Sistem Pendukung Keputusan Penentuan Nutrisi Masa Kehamilan Menggunakan Metode Analitycal Hierarcy Process (AHP) - Yusnita, Shella; Wijaya, Dhina Puspasari; Yazid, Ahmad Subhan; Pramuntadi, Andri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Many pregnant women still neglect the importance of nutrition during pregnancy, which leads to inadequate nutrient intake and increases the risk of complications such as miscarriage, low birth weight, premature birth, or infant mortality. At Gamping 1 Health Center in 2024, out of 1,793 pregnant women examined, approximately 3.35% or 60 individuals suffered from Chronic Energy Deficiency (CED) and 4.96% or 89 individuals experienced anemia. The method used is the Analytical Hierarchy Process (AHP) because it is one of the approaches that can break down complex multi-factor or multi-criteria problems into a hierarchy. Practically, this system can help pregnant women meet their daily nutritional needs optimally and support healthcare workers in providing data-based education. Thus, this DSS is expected to contribute to reducing the rates of CED and anemia among pregnant women.